2016
DOI: 10.1016/j.jbiomech.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Gait biomechanics in the era of data science

Abstract: Data science has transformed fields such as computer vision and economics. The ability of modern data science methods to extract insights from large, complex, heterogeneous, and noisy datasets is beginning to provide a powerful complement to the traditional approaches of experimental motion capture and biomechanical modeling. The purpose of this article is to provide a perspective on how data science methods can be incorporated into our field to advance our understanding of gait biomechanics and improve treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…A sample of 291 injured, and healthy runners were queried from an existing database of running kinematics . Participants were recruited through standard advertisements (eg, posters, facebook posts) approved by the Ethics Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of 291 injured, and healthy runners were queried from an existing database of running kinematics . Participants were recruited through standard advertisements (eg, posters, facebook posts) approved by the Ethics Board.…”
Section: Methodsmentioning
confidence: 99%
“…A sample of 291 injured, and healthy runners were queried from an existing database of running kinematics. 19,20 Participants were recruited through standard advertisements (eg, posters, facebook posts) approved by the Ethics Board. In this study, runners were identified for inclusion provided they: (a) had 3D gait analysis performed by the same experienced clinician using the same motion capture system, (b) were known to be injury free for the 6 months preceding data collection (25 runners) or were suffering some form of lower body injury at the time of data collection (266 runners) and (c) contained complete kinematic data with no missing values.…”
Section: Participantsmentioning
confidence: 99%
“…Given the relationship between functional disorders and nonspecific back pain, the authors believe in the importance of diagnostic procedures to evaluate the quality of movement and in the need to conduct scientific and research works in this area. Particularly, in the era of time-space research technologies, procedures should be focused on the implementation of measurable, objective, noninvasive, and economic rehabilitation methods [145][146][147].…”
Section: Stabilization Of the Patient's Condition And Stabilizationmentioning
confidence: 99%
“…While comprising the database with healthy adults is ideal in the case of the current study involving a single healthy runner free of lower limb pathology, care must be taken when applying the placement feedback to individuals with surgical changes, or developmental disorders affecting posture or anatomical alignment. However, one of the strengths of the feedback tool is that the reference database can be easily adjusted and expanded to include more individuals that possess similar morphological characteristics to the target individual (Ferber, Osis, Hicks, & Delp, 2016;Osis et al, 2016). In a similar fashion, the study's outcomes must be interpreted within the context of the JCS used, which may vary between research groups.…”
Section: Limitationsmentioning
confidence: 99%